What the Editor of an Academic Journal Expects from Authors. - Vance, L. L. (The Accounting Review, 1966)
Abstract The basic requirement of every academic editor is that each article be a scholarly contribution to knowledge of the field. Contributions in an academic journal may be made by recognizing new problems of the field and suggesting possible solutions. Opportunities for contributions comes when new techniques are devised or become available for the solution of old problems, or when some new programs or new thoughts not always forthcoming as promptly to avoid a new problem. Another type of scholarly contribution may be made in the form of historical analyses. Another dubious candidate for scholarly effort is the voluminous compendium of what others have said on a subject with no adequate or new criticism or evaluation. Manuscripts submitted by authors usually go to the printer in the case of an academic journal, so it should be clear and readable to the editor also. Editor's do have obligations, therefore, a broad view of the possible forms of scholarly contribution is also needed by the editor of a scholarly journal, certainly if the journal is designed for a fairly large and diversified audience.